FRI0617 Uptake on flu and pneumonia vaccination at the rheumatology clinic at a uk district general hospital- are we better than 10 years ago?. (12th June 2018) - Ntatsaki, E.; Tahir, A.; Jiskani, A.; Mohammed, A.; Vassiliou, V.; Watts, R.
Abstract : Background: Patients with rheumatic diseases are at increased risk of contracting infection due to the disease itslef or because of the use of immunomodulatory medication. EULAR has developed recommendations and supports vaccination against influenza and pneumococcal infections in immunocompromised patents 1 . Despite convincing data regarding the efficacy of vaccination with the use of disease-modifying anti rheumatic drugs (DMARDs), previously published data from our trust in 2007 showed that uptake of vaccination was suboptimal especially in those aged <65 years 2 . Objectives: To establish the influenza or pneumococcal (pneumovax) vaccination uptake and explore reasons for reduced uptake in patients attending a rheumatology clinic. Methods: Prospective audit of 100 patients attending the Rheumatology clinic in a UK district hospital using an anonymised survey during November to December 2017 and comparison with the data of 10 years ago. Results: A total of 100 questionnaires were given out, with return rate of 98%. Female:male ratio was 3.8:1, mean age 55±17. Most patients were treated for RA (24%), Psoriatic arthritis (20%), Ankylosing spondylitis (14%) and others, see figure 1. Regarding immunosuppression 16% were on biologics and 78% on DMARDS. Most were on methotrexate (26%), Prednisolone (16%), hydroxychloroquinine (12%), sulfasalazine (12%) whereas biologics were <10 % each (see figure 1). With regards to vaccination for influenza, overall 47% had received the vaccine (see table 1). Of those who did not take the vaccine 35% had an allergy or did not believe it was effective, but 65% were not offered the vaccine. A total of 52% commented that a health professional had discussed influenza vaccination with them, 42% mentioned that this was never discussed and 6% were unsure. In RA population uptake was 48% compared to 44% 10 years ago (p=0.81). Regarding pneumovax 29% commented that a health professional had discussed pneumococcal vaccination and only 28% had received the vaccine. Of those who did not take the vaccine 12% had an allergy or did not believe it was effective, and 83% were not aware that the vaccine existed or were not offered the vaccine. In RA population uptake was 61% compared to 62% 10 years ago (p=0.62). RA patients had better vaccination than psoriatic patients for influenza (p=0.03), but not pneumovax (p=0.52). Conclusions: Although this is a small audit conducted in a routine rheumatology clinic in the UK, it is of concern that with increased patient education seen in the last 10 years, vaccination for influenza and pneumococcus has not improved. Perhaps healthcare professionals are not discussing this with the patients sufficiently. Further patient and healthcare involvement is required to reverse the declining trend and protect our patients. References: 1. van Assen S, et al. EULAR recommendations for vaccination in adult patients with autoimmune inflammatory rheumatic diseases. Ann Rheum Dis2011;70:414–22. 2. Pradeep J, et al. Audit on the uptake of influenza and pneumococcal vaccination in patients with RA. Ann Rheum Dis2007;66:837–8. Disclosure of Interest: None declared